System Availability Assessment and Optimization of Repairable Cooling Module of HVAC System using PSO Algorithm - Chaudhary, Rajneesh; Tewari, P.C.; Modgil, Vikas (Journal of physics. Conference series, 2019)
Availability is the main scopes of system execution under the explicit states of working. Any mechanical system contains subsystems orchestrated in arrangement, parallel or half and half setup of the subsystems. Along these lines, the concern for achieving higher availability in manufacturing activities has a significant role. In the proposed research work deals with numerical and simulation modeling of condenser manufacturing system along with its subsystems. These numerical equations are solved by using the Markov Model (MM) with normalizing conditions. Also, the study has attempted to present an effective tool for improving the quality of condenser manifold assembly by executing a meta-heuristic algorithm i.e. Particle Swarm Optimization (PSO). The performances of each subsystem are analyzed by its Failure Rate (FR) and Repair Rate (RR), the optimal FR and RR is achieved by the proposed PSO algorithm and its efficiency is compared with the existing algorithm.